ChemInform Abstract: Directed Magnesiation of Polyhaloaromatics Using the Tetramethylpiperidylmagnesium Reagents TMP2Mg·2LiCl and TMPMgCl·LiCl. Issue 42 (1st October 2013) - Unsinn, Andreas; Rohbogner, Christoph J.; Knochel, Paul
Abstract The regioselective magnesiation of haloarenes (I) and (XI) followed by reaction of the resulting Grignard reagents with different electrophiles provides access to a variety of functionalized polyhaloarenes.